Evaluation of the microgrinding procedure for the microscopic analysis of temporal bones. (4th March 2017) - Cisneros, J. C.; Brito, R. de; Martins, G. S. de; Candido, N.; Ferraz, R.; Bento, R.
Abstract : Introduction : The microgrinding technique is used to study cochlear implant electrode positioning and cochlear trauma. It may be argued that this technique might cause damage to inner cochlear structures even without a cochlear implant insertion and thus it should not be recommended. Most papers do not explain how microgrinding is performed, referring to older papers for its description. Properly describing the technique and re-evaluating its safety may reassure researchers of their findings when studying trauma after cochlear implant insertion. Objective : To accurately describe the microgrinding technique and re-evaluate its safety to assess intracochlear trauma by studying non-implanted temporal bones. Methods : Four fresh temporal bones were removed before 24 hours postmortem and frozen at −20°C. Two were prepared for microgrinding before 24 hours of freezing and the others after 6 months. A descriptive analysis of the microscopic anatomy was performed, as well as a comparison between the bones processed within 24 hours of freezing and the bones frozen for 6 months. Results : A total of 80 surfaces was evaluated. Preservation of even the most delicate intracochlear and vestibular structures was observed, such as the crista ampullaris, Reissner's and basilar membranes, permitting an adequate micro-anatomical study. Artifacts were rare and did not interfere with the analysis. Bones studied before 24 hours postmortem exhibited better quality than those frozen for 6 months. Conclusions : The microgrinding technique accurately preserves the inner ear's membranous microscopic anatomy and thus it is useful to study cochlear implant electrode positioning and trauma inside the cochlea. Studies that aim to evaluate inner ear microanatomy should be performed with fresh bones or bones frozen for less than 24 hours since they exhibit a better micro-anatomical quality.